The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.29252/ibj.24.6.342
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Derived from Human Umbilical Cord Perivascular Cells Improve Functional Recovery in Brain Ischemic Rat via the Inhibition of Apoptosis

Abstract: Background: Ischemic stroke, as a health problem caused by the reduced blood supply to the brain, can lead to the neuronal death. The number of reliable therapies for stroke is limited. MSCs exhibit therapeutic achievement. A major limitation of MSC application in cell therapy is the short survival span. MSCs affect target tissues through the secretion of many paracrine agents including EVs. This study aimed to investigate the effect of HUCPVCs-derived EVs on apoptosis, functional recovery, and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…By providing trophic, vasoactive, and immunomodulatory factors in injured neurons and microglia, MSC-Exos inhibit detrimental immune response and promote neurogenesis and neuritogenesis [ 35 ]. Accordingly, several lines of evidence demonstrated that MSC-Exos efficiently improved cognition, learning deficiency, and memory loss in damaged and ischemic hippocampal neurons [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Msc-exos-dependent Improvement Of Cognitive Dysfunction Fmentioning
confidence: 99%
See 1 more Smart Citation
“…By providing trophic, vasoactive, and immunomodulatory factors in injured neurons and microglia, MSC-Exos inhibit detrimental immune response and promote neurogenesis and neuritogenesis [ 35 ]. Accordingly, several lines of evidence demonstrated that MSC-Exos efficiently improved cognition, learning deficiency, and memory loss in damaged and ischemic hippocampal neurons [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Msc-exos-dependent Improvement Of Cognitive Dysfunction Fmentioning
confidence: 99%
“…Yang and colleagues showed that MSC-Exos improved postoperative cognitive dysfunction, a severe complication of cardiopulmonary bypass, by reducing hippocampal neuronal apoptosis [ 42 ]. MSC-Exo-dependent prevention of apoptosis was also responsible for improved cognitive function of rats suffering from ischemic brain injury [ 43 ]. MSC-Exos down-regulated expression of pro-apoptotic molecules (Bax, caspase-3 and -9) and enhanced expression of anti-apoptotic Bcl-2 protein, which significantly reduced the total number of dead neurons and increased neuronal density in the ischemic boundary zone [ 43 ].…”
Section: Msc-exos-dependent Improvement Of Cognitive Dysfunction Fmentioning
confidence: 99%
“…There were 20 studies were included in the meta-analysis (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). All articles were published between 2015 and 2023.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Systemic injection of exosomes has been found to be effective in the transfer of small interfering RNA (siRNA) into the mice brain [ 79 ]. Given their implications in both physiological and pathological processes, it can be helpful to establish beneficial preventive plans and design successful therapeutic alternatives, either to mimic EVs or engineering them for a new purpose [ 27 , 80 ].…”
Section: Evs In/of Cnsmentioning
confidence: 99%